2015
DOI: 10.1007/s11258-015-0449-9
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory of native and exotic North-American prairie grasses by nymph Melanoplus grasshoppers

Abstract: Although the general interaction between native and exotic plants and specialist insect herbivores has received considerable attention in ecological studies, plant responses to herbivory by generalist insects, as well as feeding preferences of generalist insects, are still poorly understood. Experimental studies comparing leaf damage of native and exotic plants to generalist insects have provided inconsistent results due to irregularities in methodology such as using only one type of experiment or using nonsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
(79 reference statements)
0
14
0
Order By: Relevance
“…Generalist herbivores may be more likely to feed on novel plant species than forage-specialized arthropods (Strong et al 1984;Tallamy 2004). Consequently, taxa dominated by polyphagous species might be less vulnerable to invasions that displace their native food sources, especially if nonnative grasses lack effective defenses against evolutionarily novel herbivores (Parker et al 2006;Avanesyan and Culley 2015). They might even increase in abundance if nonnative plants produce more biomass than native species.…”
Section: Discussionmentioning
confidence: 99%
“…Generalist herbivores may be more likely to feed on novel plant species than forage-specialized arthropods (Strong et al 1984;Tallamy 2004). Consequently, taxa dominated by polyphagous species might be less vulnerable to invasions that displace their native food sources, especially if nonnative grasses lack effective defenses against evolutionarily novel herbivores (Parker et al 2006;Avanesyan and Culley 2015). They might even increase in abundance if nonnative plants produce more biomass than native species.…”
Section: Discussionmentioning
confidence: 99%
“…The average of all units was 14.4 cm ±3.9 with no treatment differences. At each defoliation event, the vegetation was cut down by 1/6 of the pretreatment median height in each individual defoliation unit to simulate the effect of foliar insect herbivores such as grasshoppers (e.g., Avanesyan and Culley ). Thus, by the end of the treatment, the defoliation had removed 2/3 of the original vegetation, and the median height was approximately 8–10 cm above the soil, depending on the original median height.…”
Section: Methodsmentioning
confidence: 99%
“…The biotic resistance hypothesis is particularly well explored in studies on invasive plants [20], and it predicts that native generalist herbivores will prefer to feed on introduced plants that do not share coevolutionary history with these native herbivores, and, therefore, will be less defended compared to native plants [18]. Following Maron and Vilà [18], many studies published in subsequent years demonstrated that exotic plants can be preferentially consumed in a plant’s introduced range by non-coevolved native herbivores [11,19,21,22,23,24,25,26,27,28]. Similar results on generalist herbivores’ preferences for exotic plants were also obtained from studies on non-insect invertebrates [29].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors emphasized that by incorporating exotic plants into their diet, native generalist insect herbivores can contribute to the biotic resistance of native communities to plant invasions [19,22,25,27,28]. In this regard, orthopterans, which are the most abundant aboveground insects [30], and particularly grasshoppers, are especially unique study organisms for exploring the role of native generalist insect herbivores in the biotic resistance of native communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation